Polymerization of Acrylamide N-methylene Lactic and Glycolic Acid (Baghdad Science Journal, 2023)
In this research work, the novel polymer base on acrylamide N-methylene lactic and glycolic acid was synthesized and its structural performances were identified by the IR, 1H NMR and 13C NMR spectroscopic investigations. The influencing factors and kinetics of polymerization, viscosity performance were studied and quantum chemical calculations were used to identify the correlation between the structure and properties. It was determined that the polymerization rate of the examined monomers in an aqueous solution, in the presence of DAA, adheres to the standard rules for radical polymerization of acrylamide monomers in solution. An investigation into the pH solution's impact on the kinetics of radical polymerization of acrylamido-N-methylene glycolic and acrylamido-N-methylene lactic acids revealed an extreme dependence with a minimum in a neutral medium. It was found the linear correlation between pH and viscosity. The physical and chemical performance of this polymer depends on the structural parameters related the results of quantum chemical calculation. Biological tests conducted on polyacrylamido-N-methylene lactic acid indicated its potential as a plant growth stimulator. The polymeric form of lactic acid was found to enhance the growth of Dustlik variety wheat seedlings by 40% more efficiently than lactic acid alone.